PhD thesis - Lutchyn, Roman (Kinetics of Superconducting Quantum Circuits, 2007)
Superconducting circuits exhibit quantum properties on a macroscopic scale, and are natural candidates for solid state quantum computing. Their low-energy physics can be described in terms of the phase of the order parameter, a single collective degree of freedom associated with billions of coherently paired electrons. In practice, however, on top of the superfluid condensate there are single-particle excitations (quasiparticles) with a continuous energy spectrum; the quasiparticles are coupled to the phase degree of freedom. The presence of quasiparticles in the system sets serious constraints on the performance of superconducting charge qubits. In this thesis, we study the kinetics of superconducting quantum circuits, and discuss the fundamental limitations on the energy and phase relaxation times in the presence of quasiparticles.